2021
DOI: 10.1136/bmjopen-2021-049187
|View full text |Cite
|
Sign up to set email alerts
|

Non-home discharge after cardiac surgery in Australia and New Zealand: a cross-sectional study

Abstract: ObjectiveTo determine the proportion of patients surviving their cardiac surgery who experienced non-home discharge (NHD) over a 16-year period in Australia and New Zealand (ANZ).DesignRetrospective, multicentre, cross-sectional study over the time period 01 January 2004 to 31 December 2019.SettingAdult patients who underwent cardiac surgery from the Australia New Zealand Intensive Care Society Adult Patient Database (APD).ParticipantsAdult patients (age 18 and above) who underwent index coronary artery bypass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Age, ANZROD, type of surgery (CABG, valve, CABG + valve), the urgency of surgery (elective, non-elective), hospital type (public, private), and country (Australia, New Zealand) were entered as xed effects. Variable selection was performed based on previous work in this eld and known associations with mortality in this patient group (10). Results are presented as an odds ratio (OR) with a 95% con dence interval (CI).…”
Section: Discussionmentioning
confidence: 99%
“…Age, ANZROD, type of surgery (CABG, valve, CABG + valve), the urgency of surgery (elective, non-elective), hospital type (public, private), and country (Australia, New Zealand) were entered as xed effects. Variable selection was performed based on previous work in this eld and known associations with mortality in this patient group (10). Results are presented as an odds ratio (OR) with a 95% con dence interval (CI).…”
Section: Discussionmentioning
confidence: 99%
“…NHD is a composite measure with an individual patient-centered outcome, and it is associated with patient disability or impaired organ function, which means they are not allowed to discharge the patients to their homes. In a recent study, NHD after cardiac surgery was found to be 7% [ 21 ] and was associated with decreased overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The impact on enhancing recovery and long-term outcomes must incorporate additional patient factors and selection criteria, optimal device utilization to include data on myocardial performance, duration and doses of inotropes [112], the stages of AKI [113], various ventilation tactics and timing, mobility, mortality, rescue and failure to rescue [114], ICU and total LOS, readmissions, as well as patient-reported outcomes [29,115,116 && ]. Areas of burgeoning interest and opportunity also include wearable technologies [117][118][119][120][121], novel digital technologies with intelligent computing algorithms [122], virtual ICUs (where the rare expertise with tMCS may be leveraged via technology) [123], discharge location [124], time at home, remote monitoring [125,126], and cardiac rehabilitation [127,128].…”
Section: Near Futurementioning
confidence: 99%
“…Areas of burgeoning interest and opportunity also include wearable technologies [117–121], novel digital technologies with intelligent computing algorithms [122], virtual ICUs (where the rare expertise with tMCS may be leveraged via technology) [123], discharge location [124], time at home, remote monitoring [125,126], and cardiac rehabilitation [127,128].…”
Section: Introductionmentioning
confidence: 99%